The Role of Tawḥīd Values in Shaping Islamic Character among Malay Communities of the Archipelago - Sa’diah, Halimatu; Riadi, Haris; Marlizayani, Marlizayani; Faridah, Faridah (Research, Training and Philanthropy Institution Natural Aceh, 2025)
Before the arrival of Islam, the Malay community was known to adhere to animism and dynamism and was influenced by Hindu and Buddhist teachings. Religious transformation began when Islam entered through trade routes, with Arab traders as the bearers of the teachings of monotheism. The values of the monotheistic creed that were gradually instilled not only changed the belief system of the Malay community but also shaped the identity and character of Islam. This study aims to examine the role of the values of the monotheistic creed in shaping the character of Islam within the Malay community, which is integrated with local culture. This study employs a descriptive qualitative approach, utilizing a library research method that involves examining academic literature, historical documents, and local cultural sources. The results of the study indicate that the monotheistic creed makes a significant contribution to shaping the character of a faithful, sincere, responsible, disciplined person who upholds the values of divinity. The monotheistic creed also strengthens the identity of Malay Islam and serves as a moral foundation in community life. The implications of this study suggest that understanding and strengthening the values of monotheism rooted in local culture can be utilized as an effective, wisdom-based character education strategy in responding to moral challenges in the modern era.